2019
DOI: 10.3390/f10050367
|View full text |Cite
|
Sign up to set email alerts
|

Patchy Fires Promote Regeneration of Longleaf Pine (Pinus palustris Mill.) in Pine Savannas

Abstract: Research Highlights: Spatial patterns of fire spread and severity influence survival of juvenile pines in longleaf pine savannas. Small areas that do not burn during frequent fires facilitate formation of patches of even-aged longleaf pine juveniles. These regeneration patches are especially associated with inner portions of openings (gaps) and where canopy trees have died in recent decades. Patterns of prescribed fire can thus have an important influence on stand dynamics of the dominant tree in pine savannas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 77 publications
0
41
0
Order By: Relevance
“…Previous studies have demonstrated that fire behavior (e.g., season, intensity, patchiness) significantly affected the mortality of longleaf pine grass stage seedlings (e.g., [7,25]). Consequently, we acknowledged that the absolute fire-induced mortality rate of longleaf pine seedlings was necessarily varying with fire behavior that is largely determined by the weather conditions and fuel properties during the burn.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that fire behavior (e.g., season, intensity, patchiness) significantly affected the mortality of longleaf pine grass stage seedlings (e.g., [7,25]). Consequently, we acknowledged that the absolute fire-induced mortality rate of longleaf pine seedlings was necessarily varying with fire behavior that is largely determined by the weather conditions and fuel properties during the burn.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the studied forest was planted and had a relatively uniform distribution of longleaf pine trees. With needle litter, the main fuel component, cast evenly on the ground, fire may have burned uniformly and impacted all seedlings [36], making survival due to fire escape (i.e., on the unburned spots) less likely [25]. Therefore, the mortality estimation from this study might represent the upper threshold of fire-induced mortality for seedlings of the same size.…”
Section: Seedling Size and Fire Survivalmentioning
confidence: 99%
See 3 more Smart Citations